Expressions of Attitudes in Students’ Narrative Writing: An Appraisal Analysis - Fitriati, Sri Wuli; Solihah, Yuni Awalaturrohmah; Tusino, Tusino (Lingua Cultura, 2018)
This article investigated attitude, one of subsystem appraisal, in the English as a Foreign Language (EFL) university students’ narrative writings. Five narrative writing was selected purposefully from undergraduate students of the English Department at a local private university in Central Java. The findings demonstrate that the affect is the most dominant subsystem of attitude used in the students’ narrative writing to convey feelings and emotion of characters and events in the stories in order to make the readers involved in the stories. The prominent finding of this research implies that most students used expressions of attitudes which belong to basic English words and repetition of same words. This present research suggests English language teachers and lecturers pay more attention to the explicit teaching of attitudinal words usage in writing, especially narrative writing.